Teleworking While Sick: A Three-Wave Study of Psychosocial Safety Climate, Psychological Demands, and Presenteeism - Biron, Caroline; Karanika-Murray, Maria; Ivers, Hans; Salvoni, Sandra; Fernet, Claude (Frontiers in Psychology, 2021)
The COVID-19 pandemic has led to a significant increase in the proportion of employees for whom teleworking became mandatory. Presenteeism, or the behavior of working while ill, has hardly been studied in the context of telework. The pandemic forced millions of workers to abruptly transition to working from home for a prolonged period of time, leaving employers often unaware of their workers’ health status or work capacity. This change also eroded the work experience itself, the workplace, and their protective impact on both individual health and work outcomes. This study focused on the longitudinal relationships among psychosocial safety climate (PSC), a lead indicator of workplace conditions, psychological demands, an indicator of quality of work, and presenteeism among a representative sample of teleworkers. PSC was expected to have an indirect impact on presenteeism with psychological demands as a mediator of this impact. Method. We collected data from a representative sample of teleworkers during the first months (T1: April, T2: June, T3: December 2020) of the pandemic using a three-wave online survey (N = 275). We tested a model of PSC as a determinant of presenteeism in teleworkers with psychological demands as a mediator. A cross-lagged panel model was estimated to test cross-sectional and longitudinal relationships. Findings. As expected, psychological demands increased over time. Contrary to expectations, presenteeism prevalence remained unchanged while PSC increased over time. The data fully supported the mediating effect of psychological demands, such that a higher evaluation of PSC at T1 led to lower psychological demands at T2, which led to reduced presenteeism at T3. We also found a reciprocal relationship, with higher psychological demands at T2 leading to decreased evaluation of PSC at T3. These results show that teleworkers’ perception of their organization as giving high priority to their psychological health is an important determinant of their work experience, ultimately influencing their decision to work while ill. The context of the pandemic has highlighted the importance of a positive workplace climate and working conditions for reducing behaviors that can be harmful to health and productivity. Implications for theory and practice, beyond the pandemic, are discussed.